ICT fusion on the relationship between resource transformation capabilities and quality management practices among SMEs in Uganda - Benard Onyinyi; Will Kaberuka (Cogent Business & Management, 2019)
The major objective of this study was to determine the relationship between resource transformation capabilities and quality management practices under conditions of varying levels of Information and Communication Technology (ICT) fusion among Small and Medium Scale Enterprises (SMEs). Data were collected using cross-sectional and descriptive survey designs; which involved 210 SMEs selected from the Central and Eastern regions of Uganda. Hierarchical regression models and a mod-graph were used in the analysis. The results reveal that the influence of resource transformation capabilities on quality management practices varies with the level of ICT fusion among SMEs. Further, there exists a positive and significant relationship between resource transformation capabilities and quality management practices. Based on findings, it is imperative for managers to re-tool their employees with modern ICT applications to strengthen the relationship between resource transformation capabilities and quality management practices among SMEs.
Keywords: 650; SMEs; resource transformation capabilities; information and communication technology; quality management practices